2009
DOI: 10.1002/chem.200902408
|View full text |Cite
|
Sign up to set email alerts
|

First Heterotrimetallic {3 d‐4 d‐4 f} Single Chain Magnet, Constructed from Anisotropic High‐Spin Heterometallic Nodes and Paramagnetic Spacers

Abstract: Dedicated to Dr. Jean-Pierre Costes as a tribute to his contributions to the development of the chemistry and magnetism of 3d-4f complexesPolymetallic complexes are more and more involved in materials science. The metal ions exert a functional role, carrying magnetic, optical, or redox properties, and a structural one, directing and sustaining the overall architecture of the polymetallic systems. The use of different metal ions in constructing coordination compounds brings novel properties that are not exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
115
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 206 publications
(118 citation statements)
references
References 88 publications
(35 reference statements)
3
115
0
Order By: Relevance
“…It was confirmed that this striking phenomenon is not in conflict with the OYA criterion (1) and may be a direct result of different Landé g-factors of magnetic particles [39][40][41][42][43], quenched disorder [44][45][46] or doping by itinerant particles [47][48][49][50][51]. In the last case, a change of the particle concentration may allow one to tune the value and position of the magnetization plateau in a controlled way.…”
Section: Introductionmentioning
confidence: 59%
“…It was confirmed that this striking phenomenon is not in conflict with the OYA criterion (1) and may be a direct result of different Landé g-factors of magnetic particles [39][40][41][42][43], quenched disorder [44][45][46] or doping by itinerant particles [47][48][49][50][51]. In the last case, a change of the particle concentration may allow one to tune the value and position of the magnetization plateau in a controlled way.…”
Section: Introductionmentioning
confidence: 59%
“…14) [90,91]. The latter site binds a Ln(III) ion so the resulting SCMs contain a 3d-4f building block (Fig.…”
Section: Salen-type Schiff Base Complexesmentioning
confidence: 99%
“…Various variants of the Ising-Heisenberg chains have been examined: diamond-chain, [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] saw-tooth chain, 29,30 orthogonal-dimer chain, [31][32][33] tetrahedral chain, [34][35][36][37][38] and some special examples relevant to real magnetic materials. [39][40][41][42] In the present work, we will rigorously examine a magnetization process of a few quantum Heisenberg spin clusters and Ising-Heisenberg diamond chain, which will not display strict magnetization plateaus on assumption that some constituent spins have different Landé g-factors and may be a XY-anisotropy of the exchange interaction. Also, the Dzyaloshinskii-Moriya (DM) term in a direction different from that of the magnetic field can lead to the same effect.…”
Section: Introductionmentioning
confidence: 99%